Surprised by love : a novel - Lessman, Julie, 1950- (Lessman, Julie, 1950- Heart of San Francisco, 2014)
When Megan McClare turns to Bram Hughes for support and advice, Bram develops a sudden unwelcome attraction to a girl he had always thought of as a kid sister. He advises forgiveness, but can he forgive himself for pushing the woman he loves into the arms of another man?